Effects of his-tags on physical properties of parvalbumins. (January 2019) - Vologzhannikova, Alisa A.; Khorn, Polina A.; Kazakov, Alexei S.; Permyakov, Eugene A.; Uversky, Vladimir N.; Permyakov, Sergei E.
Graphical abstract: Highlights: Parvalbumin (PA) is a member of the EF-hand family of calcium binding proteins. His-tag attachment differently changed secondary structure of apo- and holo-forms. His-tag attachment differently affected hydrodynamic radii of apo- and holo-forms. His-tag attachment increased thermal stability of apo- and holo-forms of PA. These facts should be taken into consideration while analyzing His-tagged Pas. Abstract: A comparative study of His-tagged and non-tagged rat β-parvalbumin (rWT β-PA), calcium binding protein with the EF-hand calcium binding domains, has been carried out. The attachment of His-tag increases α-helical content and decreases β-sheets and β-turns content of the metal free form (apo-state) of β-PA. In contrast to this, the attachment of His-tag decreases α-helical content by more than 10% and increases contents of β-sheets and β-turns of the Ca 2+ -loaded state. According to the dynamic light scattering analysis, apo-state of His-tagged rat β-PA seems to be less compact compared with the apo-state of non-tagged rat β-PA. Surprisingly, the attachment of His-tag practically does not change mean hydrodynamic radius of Ca 2+ -loaded rat β-PA. The attachment of His-tag shifts thermal denaturation peaks of both apo- and Ca 2+ -loaded states of rat β-PA towards higher temperatures by 3–4 °C and slightly decreases its Ca 2+ affinity. These results should be taken into consideration in the use of His-tagged parvalbumins.